2008
DOI: 10.1039/b809737b
|View full text |Cite
|
Sign up to set email alerts
|

Gold single-crystal electrode surface modified with self-assembled monolayers for electron tunneling with bilirubin oxidase

Abstract: Using Au(111) and Au(100) single-crystal electrodes modified with self-assembled monolayers (SAMs), the direct electron transfer reaction of bilirubin oxidase (BOD) adsorbed onto their surfaces was investigated. The BOD adsorbed onto the Au(111), Au(100) and gold /mica electrodes, and the BOD adsorbed onto Au(111) electrodes modified with C(3)-SO(3)H and C(n)-COOH (n = 2, 5 and 7), showed the electrocatalytic currents of dioxygen reduction based on the direct electron transfer reaction. The BOD adsorbed onto A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 57 publications
4
64
0
Order By: Relevance
“…[47] A clearer situation was obtained upon immobilization of Mv BOD on gold single-crystal electrodes. [158,177] CV coupled to QCM and AFM experiments at various SAMs confirmed that hydrophilic interfaces, and especially negative interfaces, were more favorable for T1 interaction and electrocatalysis of O 2 reduction. A different orientation on bare gold vs. SAM-modified gold was suggested.…”
Section: Multicopper Oxidases (Mcos)mentioning
confidence: 96%
“…[47] A clearer situation was obtained upon immobilization of Mv BOD on gold single-crystal electrodes. [158,177] CV coupled to QCM and AFM experiments at various SAMs confirmed that hydrophilic interfaces, and especially negative interfaces, were more favorable for T1 interaction and electrocatalysis of O 2 reduction. A different orientation on bare gold vs. SAM-modified gold was suggested.…”
Section: Multicopper Oxidases (Mcos)mentioning
confidence: 96%
“…Previous reports have described DET of BOD on bare or negatively charged SAMs modified single-crystal electrodes [101] and three-dimensional AuNP electrodes [102]. BOD was physically embedded into bare NPG and the resulted electrodes displayed bioelectrocatalytic reduction of molecular oxygen, undergoing efficient DET (Figure 8) [76].…”
Section: Multi-copper Oxidasesmentioning
confidence: 99%
“…The catalysis of O 2 reduction by this enzyme has been studied several times. DET 53 Catalytic currents were found for bare (single-crystal) gold and gold modified with different SAMs. Negatively charged SAMs (ÀCOOH and ÀSO 3 À ) were found to give catalytic current, whereas SAMs terminated by ÀCH 3 , ÀOH, or ÀNH 2 did not show any.…”
Section: Introductionmentioning
confidence: 99%